Transverse Distribution of Pump Power in the Diode-laser Side-pumped Solid-state Laser Rod - Luu, Mai Van; Khoa, Dinh Xuan; Sau, Vu Ngoc; Quy, Ho Quang (Communications in Physics, 2009)
Based on the assumption that Gaussian pump power of diode laser bar is the same at any cross-section along the laser rod and its curvated surface plays as thin lens, the expression describing the pump intensity distribution inside laser rod was obtained by transfer matrix. To have the cross-section of active volume or excited volume coincides with one of laser mode volume, the dependence of pump intensity distribution on location of outside pump beams is investigated by simulation.